Optimasi Query pada sistem informasi pencatatan aktifitas perubahan data nilai mahasiswa - nilaliliana prihatin; dwi sakethi; febi eka febriansyah (Jurnal Komputasi, 2016)
A large amount of data can affect the search process the data in a database. The greater the amount of data, then the data search process will take longer. In a process of value management, activity data changes the value of an activity that is often overlooked by managers value. This system is used to listing activites done by student grades manager. The recording process will make the amount of data increases and pencarianya time it will take substantial time. The prior research explained that relational operators combined with indexing strategy in sub query has a better performance compared to using the other methods. This research using indexing strategy and nested query for activity listing information system for student grades data changes. The process of system testing conducted several experiments such as comparing data using index and data that did not use the index (table scan) to several conditions, namely the data on the amount of 517, 980, 2369, and 4221. Nested query testing and regular query or query were tested directly using the same amount of data and applied on subjects data search. Indexing strategy that is applied to the big amount of data will generate faster execution time than a search without indexing strategy, in contrary to the small amount of data indexing strategy does not really affect the search process. The use of nested query in the subjects data search will be faster than the search time regular query or query directly.